2015
DOI: 10.1007/s12035-015-9135-0
|View full text |Cite
|
Sign up to set email alerts
|

Ras Activity Oscillates in the Mouse Suprachiasmatic Nucleus and Modulates Circadian Clock Dynamics

Abstract: Circadian rhythms, generated in the mouse suprachiasmatic nucleus (SCN), are synchronized to the environmental day-night changes by photic input. The activation of the extracellular signal-regulated kinases 1 and 2 (ERK1,2) and cAMP response element-binding protein (CREB)-mediated transcription play a critical role in this photoentrainment. The small GTPase Ras is one of the major upstream regulators of the ERK1,2/CREB pathway. In contrast to the well-described role of Ras in structural and functional synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Interestingly, we have demonstrated light-induced regulation of the Ras signaling cascade (Serchov and Heumann, 2006;Serchov et al, 2015b). In order to study the role of Ras, we have generated a transgenic mouse model expressing constitutively activated Ras selectively in neurons (synRas mice) (Heumann et al, 2000).…”
Section: Bdnf/ras/erkmediated Regulation Of Homer1a In Depressionmentioning
confidence: 99%
“…Interestingly, we have demonstrated light-induced regulation of the Ras signaling cascade (Serchov and Heumann, 2006;Serchov et al, 2015b). In order to study the role of Ras, we have generated a transgenic mouse model expressing constitutively activated Ras selectively in neurons (synRas mice) (Heumann et al, 2000).…”
Section: Bdnf/ras/erkmediated Regulation Of Homer1a In Depressionmentioning
confidence: 99%
“…Both experimental data and bioinformatic analysis suggest that oncogenic RAS proteins are involved in the deregulation of the circadian clock in cancer cells (53). Finally, it was recently shown that RASsignaling affects the circadian clock in the suprachiasmatic nucleus of mice acting, at least partially, via ERK and glycogen synthase kinase (GSK), and thereby fine-tunes the circadian period (54). Our goal in this study was to investigate whether RAS2 is involved in the metabolic compensation of the circadian clock of Neurospora crassa.…”
Section: Introductionmentioning
confidence: 99%
“…A potential mammalian link is the role of the Ras family member, Dexras1, in the light input into the circadian clock in mice46. Other studies continue to implicate an essential role for Ras signaling in circadian rhythms in animals474849.…”
Section: Discussionmentioning
confidence: 99%